thnoveterinary Study Against Animal Trypanosomosis by Berta Community in Assosa Zone, Northwest Ethiopia - Abesh Birhanu Morka, (Indian Journal of Advanced Zoology (IJAZ), 2025)
The Berta community has utilized local medicinal plants to manage various animal diseases, including trypanosomosis, which significantly impacts livestock productivity and rural livelihoods. Traditional medicine practitioners in the Assosa Zone of Northwest Ethiopia have used various ethnoveterinary practices to control animal trypanosomosis. Thus the purpose of the current study was to document these practices in the three districts of Assosa Zone Bambasi, Homesha, and Meng Woreds. An ethnobotanical study was carried out from February 2023 to September 2024. In total, 60 respondents (41 men’s and 19 women’s) were selected using a multistage random sampling method. Data was collected using semi-structured interviews, field observations, and preference ranking. Data were analyzed using descriptive statistics, preference ranking, and informant consensus factor. The study identified 35 medicinal plants used in ethnoveterinary practices to treat animal trypanosomosis in the district. The most common family is Solanaceae (3 spp.), followed by Asteraceae (2spp.), Aloaceae (2spp.), Barssiacea (2spp.), Fabaceae (2spp.) and Rutaceae (2spp.). The local people generally used the leaves, followed by root, and bark plant parts to prepare drugs for treating livestock trypanosomosis diseases. The great majority (48.5%) of the medicinal plant's growth form was herbs, which were mainly administered orally, and the method of preparation was crushing. The majority (65.4%) of the medicinal plants were gathered from the wild habitat. Documentation of the indigenous knowledge among medicinal plants on the treatment of animal trypanosomosis should be valuable for future phytochemical and pharmacological investigations of new veterinary.